Exit choice in an emergency evacuation scenario is influenced by exit familiarity and neighbor behavior. (July 2018) - Kinateder, Max; Comunale, Brittany; Warren, William H.
Highlights: Virtual Reality experiment testing social influence and movement to familiar during a simulated evacuation. Results confirm familiarity and social influence hypothesis and are in line with observations in field studies. Effect of social influence increases with number of bystanders. The results are discussed in the light of current literature and their implications for evacuation design and modeling. Abstract: 'Movement to the familiar' has been reported during evacuation incidents but has not yet been studied in controlled experiments. We investigate effects of exit familiarity and egress behavior of other pedestrians on exit choice in an ambulatory virtual environment. Participants walked into a virtual museum through a 'familiar' door and were asked to evacuate when a fire alarm sounded as they normally would in the real world. They were significantly more likely to exit through the familiar door than through a second available exit. This effect was greater when virtual neighbors also left by the familiar door and was reduced when neighbors left by the unfamiliar door; this social influence was stronger with two neighbors than with one. The results show that exit familiarity and neighbor behavior influence evacuation behavior, and that social influence increases with the number of neighbors. The findings have implications for modeling pedestrian evacuation and improving evacuation procedures.